A single session of aerobic exercise influences paraoxonase 1 activity and concentration - J. Kyle Taylor (RETOS. Nuevas Tendencias en Educación Física, Deporte y Recreación, 2015)
Our purpose was to examine changes in paraoxonase 1 (PON1) concentration and activity following a single aerobic exercise session. Sixteen men (32 ± 8 yrs.; BMI = 29.4 ± 6.8 kg/m2; % fat = 29 ± 13; VO2max = 38.3 ± 11.9 ml.min-1.kg-1; waist circumference = 93.7 ± 16.0 cm; HDL-C = 1.19 ± 0.21 and triglycerides = 1.22 ± 1.04 mmol’™l-1; direct LDL = 2.69 ± 0.73 mmol’™l-1) expended 400 kcals by treadmill walking at 65% of VO2max. Fasting blood samples were collected before (PRE), immediately post-exercise (IPE), 24 hours post-exercise, and 48 hours post-exercise. PON1 concentration, PON1 activity, lipids, apolipoprotein A1 (Apo A1), apolipoprotein B (Apo B), and thiobarbituric acid reactive substances (TBARS) were analyzed for each time point. The men were divided into two groups based on their body mass index (BMI): Normal weight (NW) and Obese Group. At baseline, PON1 concentration and activity were significantly higher in the NW group as compared to the obese group. In addition, PON1 activity was significantly higher in the NW group as compared to the obese group for all time points. Furthermore, PON1 concentration and activity were significantly increased in the combined group immediately post-exercise and returned to baseline levels within 24 hours. PON1 activity was significantly increased in the Obese group IPE and this was observed with increases in HDLc, Apo A1, and TBARS.